THE KALLIKREIN-KININ SYSTEM IS FALLING INTO PIECES: BRADYKININ FRAGMENTS ARE BIOLOGICAL ACTIVE PEPTIDES. (April 2021) - Souza-Silva, Igor Maciel; Paula, Cristiane; Santos, Anderson; Oliveira, Vívian; Rocha, Isabella; Antunes, Maísa; Cordeiro, Lídia; Teixeira, Vanessa; Scalzo-Júnior, Sérgio; Amaral, Flávio; Resende, Jarbas; Fontes, Marco Antônio; et al.
Abstract : Objective: Bradykinin [BK-(1–9)] is an endogenous peptide involved in many physiological and pathological processes, such as cardiovascular homeostasis and inflammation. The central dogma of the kallikrein-kinin system is that BK-(1–9) fragments are biologically inactive. In this work, we proposed to test whether these fragments were indeed inactive. Design and method: Nitric oxide (NO) was quantified in human, mouse and rat cells loaded with DAF-FM after stimulation with BK-(1–9), BK-(1–7), BK-(1–5) and BK-(1–3). We used adult male rat aortic ring preparation to test vascular reactivity mediated by BK-(1–9) fragments. Changes in blood pressure and heart rate was measured in conscious adult male rats by intraarterial catheter method. Results: BK-(1–9) induced NO production in all cell types tested by B2 receptor activation. BK-(1–7), BK-(1–5) and BK-(1–3) also induced NO production in all tested cell types but this response was independent of the activation of B1 receptor and/or B2 receptor. BK-(1–7), BK-(1–5) or BK-(1–3) induced only vasorelaxant effect and in a concentration-dependent fashion. Vasorelaxant effects for BK-(1–7), BK-(1–5) or BK-(1–3) were independent of the kinin receptors. BK-(1–9) induced in conscious adult male Wistar rats a dose-dependent hypotension while BK-(1–7), BK-(1–5) and BK-(1–3) induced a dose-independent hypotension. Importantly, these observations diverged from the BK-(1–9) results, highlighting that indeed the BK-(1–9) fragments do not seem to act via the classical kinin receptors. Conclusions: In conclusion, BK-(1–7), BK-(1–5) and BK-(1–3) are biologically active components of the kallikrein-kinin system. Importantly, observed pathophysiological outcomes of these peptides are independent of B1R and/or B2R activation.